Governance and Business-Society Relations in Areas of Limited Statehood: An Introduction. Issue 7 (September 2021) - Azizi, Sameer; Börzel, Tanja; Hansen, Hans Krause
In this introductory article we explore the relationship between statehood and governance, examining in more detail how non-state actors like MNCs, international NGOs, and indigenous authorities, often under conditions of extreme economic scarcity, ethnic diversity, social inequality and violence, take part in the making of rules and the provision of collective goods. Conceptually, we focus on the literature on Areas of Limited Statehood and discuss its usefulness in exploring how business-society relations are governed in the global South, and beyond. Building on insights from this literature, among others, the four articles included in this special issue provide rich illustrations and critical reflections on the multiple, complex and often ambiguous roles of state and non-state actors operating in contemporary Syria, Nigeria, India and Palestine, with implications for conventional understandings of CSR, stakeholders, and related conceptualizations.